(untitled) (Estudios humanísticos. Geografía, historia y arte, 1997)
The renaissancist bautismal pile of the Cathedral of Leon is decorated with various reliefs that forro an iconographical program based on ideas conected to the sacrament of the Baptism. Thus, the four scenes represent the different types of Baptism. A multiple martyrdom (probably of St. Marcelo and his sons) symbolizes the baptism by blood; the Baptism of Christ alludes to the baptism by water, and the last scene probably simbolizes the baptism by fire. Parallelly, four sculptures representing Moses, St. John the Baptist, and posibly the prophet Isaiah and one Evangelist, have been represented as biblic personages closely related to the idea of baptism. Equally, some formal aspects, like four winged heads or the scalework texture of the pile (probably simbolizing the whale of Jonah and the idea of resurrection) have the same intention. Finally, the presence of the nobiliary shield of the patron of the fond wants to significate the personal glory, fame and honour of the bishop, humanistic values joined to the personal defense of the Sacrament and its theological and liturgical importante.